Adverse Events Following Vaccination: A Review of Russian and International Terminology - A. S. Korovkin; D. V. Gorenkov (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2024)
SCIENTIFIC RELEVANCE. Inconsistent terminology for vaccine safety may create challenges for healthcare professionals in identifying, interpreting, and assessing adverse events following vaccination in clinical practice.AIM. The authors aimed to review Russian and international terminology for adverse events following vaccination. DISCUSSION. This review covers the terminology used in Russian, EAEU, WHO, and ICH documents. The term "adverse event" is used in most Russian and international pharmacovigilance regulations and guidelines; this term universally defines undesirable consequences associated with medicinal products regardless of their therapeutic class. Russian regulations and guidelines use various terms to describe adverse events following vaccination, including "adverse events", "side effects of vaccines", and "post-vaccination complications". In 2019, the Ministry of Health of Russia approved the Guidelines for the Detection, Investigation, and Prevention of Side Effects Following Immunisation. However, the term "side effects following immunisation" cannot unambiguously characterise the safety of vaccines, as this term can refer to negative, neutral, or positive events following vaccination. The term "post-vaccination complications" is defined in Russian legislation as a list of pathological conditions. The list is not exhaustive and does not fully reflect the definition of post-vaccination complications as severe and/or persistent health issues following vaccination. The term "adverse events following immunisation", which is recommended by most international guidelines, describes the negative consequences of vaccination more accurately. At the same time, the term "post-vaccination complications" can be reformulated as "serious adverse events following vaccination" with clearly defined and categorised criteria.CONCLUSIONS. In addition to aiding in detecting, classifying, and evaluating adverse events following immunisation, the unification of terminology for vaccine safety in Russian regulations and guidelines will also facilitate risk mitigation in both individual and mass vaccination campaigns in general.